Effect of the Coriolis force on bounded traveling waves of the rotation-two-component Camassa–Holm system. Issue 3 (11th February 2023) - Zhao, Keqin; Wen, Zhenshu
Abstract : In this paper, we qualitatively study the effect of the Coriolis force on traveling waves of the rotation-two-component Camassa–Holm system in the rotating fluid, which is a model in the equatorial water waves, from the perspective of dynamical systems. We obtain the explicit critical rotational speed Ω = 1 2 ( A + c ) ( A is a parameter of the system characterizing a linear underlying shear flow and c is the wave speed), which reflects the Coriolis force. Based on this critical vorticity, we obtain phase portraits of the system under exact explicit parameters conditions. Then we not only show the existence of various bounded traveling waves including smooth solitary waves, peakons and kink waves, under corresponding exact explicit parameters conditions, but also obtain their exact expressions. Of particular interest is that we find that kink waves (which were not found previouly) exist only when Ω > 1 2 ( A + c ), that is, the rotational speed Ω should be greater than 1 2 ( A + c ) .